Programmed Cell Death in the Eradication of HIV-1 Infected Cells by the Oncolytic Maraba Virus MG1 - Magro, Megan (Université d'Ottawa / University of Ottawa, 2023)
Since the start of the HIV/AIDS epidemic in 1981, 75.7 million people have become infected with HIV, and 32.7 million have died as a result. Fortunately, life-saving treatment regimens have been developed. Combination antiretroviral therapy (cART) is effective at reducing viral load to an undetectable range, thus preventing transmission of HIV. However, cART is not a cure. Latent and persistent viral reservoirs persist in vivo, and act as pools of infectious virus capable of re-activation if cART is abrogated. In the present work, we investigate the use of an oncolytic virus called MG1, which is capable of targeting and killing HIV infected CD4+ T cells and macrophages in vitro. We sought to determine the mechanism of cell death induced by MG1 to kill HIV infected cells. Our results indicate that MG1-induced cell death of HIV infected cell lines, is independent of caspases, and that caspase 3 and 7 activity is downregulated in HIV infected cell lines. We also determined that HIV infected primary monocyte-derived macrophages are preferentially killed by MG1 over the uninfected bystander cells. Ultimately, these results provide important insight towards how MG1 kills HIV infected cells in vitro, and together with future work, we hope to become one step closer to a potential cure for HIV.
Keywords: HIV; infectious disease; virology; oncolytic viruses